2006
DOI: 10.1086/507174
|View full text |Cite
|
Sign up to set email alerts
|

Extinction Columns and Intrinsic X‐Ray Spectra of the Anomalous X‐Ray Pulsars

Abstract: The X-ray spectra of anomalous X-ray pulsars have long been fit by smooth, empirical models such as the sum of a blackbody plus a power law. These reproduce the $0.5Y10 keV range well, but fail at lower and higher energies, grossly overpredicting the optical and underpredicting the hard X-ray emission. A poorly constrained source of uncertainty in determining the true, intrinsic spectra, in particular at lower energies, is the amount of interstellar extinction. In previous studies, extinction column densities … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
43
1

Year Published

2007
2007
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 37 publications
8
43
1
Order By: Relevance
“…1 we present the K s band field around the Chandra 0.8 position of 1RXS J170849-400910 (Israel et al 2004). Besides sources A and B proposed by Israel et al (2003b), Safi-Harb and West (2005) and Durant and van Kerkwijk (2006), as the possible IR counterparts to this AXP, many further faint sources (e.g. Star C and Star D) were detected strongly consistent with the Chandra uncertainty region.…”
Section: Ir Observation: Vlt-nacosupporting
confidence: 56%
See 3 more Smart Citations
“…1 we present the K s band field around the Chandra 0.8 position of 1RXS J170849-400910 (Israel et al 2004). Besides sources A and B proposed by Israel et al (2003b), Safi-Harb and West (2005) and Durant and van Kerkwijk (2006), as the possible IR counterparts to this AXP, many further faint sources (e.g. Star C and Star D) were detected strongly consistent with the Chandra uncertainty region.…”
Section: Ir Observation: Vlt-nacosupporting
confidence: 56%
“…Note that the 2.5σ variability recently reported for source B by Durant and van Kerkwijk (2006) does not seem to be a conclusive word on the IR counterpart of this source, especially considering that source B has IR magnitudes much brighter than all other AXPs.…”
Section: On 1rxs J170849-400910 Ir Counterpartmentioning
confidence: 63%
See 2 more Smart Citations
“…However, in other instances, the two fluxes were not correlated, as for 1E 1048−5937 , and Durant, van Kerkwijk, & Hulleman 2004. In 4U 0142+61, reported variations in the IR are not seen contemporaneously in our X-ray data, and are on time scales much shorter than that of the X-ray variation reported here Durant & van Kerkwijk 2006). Wang et al (2006) observed mid-IR emission from 4U 0142+61 which they argue is associated with a passive fall-back disk irradiated by the central X-ray pulsar.…”
Section: Other Wavelengthscontrasting
confidence: 62%